Cushioning mechanism of the metatarsals during landing for the skateboarding ollie maneuver - Wu, Yusen; Wang, Haichun; Deng, Cheng; Guo, Yangyu; Zhu, Xiaolan (Frontiers in Bioengineering and Biotechnology, 2024)
Skateboarding is an Olympic event with frequent jumping and landing, the cushioning effect of foot structure (i.e. arch, metatarsal bone, etc.) and the damping performance of sports equipment (i.e. shoes, insoles, etc.) will greatly affect athletes' sports performance and lower limb injury risk. Skateboarding is characterized by the formation of a "man-shoe-skateboard system", which may make its foot cushioning mechanism different from the previous studies of basketball, gymnastics broad jump and other sports. Therefore, it is necessary to clarify the cushioning mechanism of the foot structure on the landing process of skateboard. To achieve this, a multi-body finite element model of the right-foot, shoe, and skateboard was created using Mimics, Geomagic, and ANSYS. Kinetic data from Ollie was used to determine plantar pressure and Achilles tendon force at three characteristics (T1, T2 and T3). The stress and strain on the foot and MT1-5 (metatarsal bones) were then simulated. The simulation results had an error of 6.98% when compared to the actual measurements. During landing, the force exerted on the internal soft tissues tend to increase. The stress and strain variations were highest in the MT2, MT3, and MT4. Moreover, the torsion angle of MT1 was greater than that of the other metatarsals. Additionally, the displacement of the MT2, MT3, and MT4 was higher compared to the other parts. Research has found that skateboarders need to absorb the ground reaction force through the movement of the MTs when Ollie lands. The soft tissues, bones, and ligaments in the front of the foot may have a high risk of injury. The developed model serves as a valuable tool for analyzing the foot mechanism in skateboarding. In the design of skateboard shoes, it is crucial to enhance cushioning in the front foot to reduce potential injuries.